(untitled) (Damascus University Journal of agriculture sciences, 2021)
Orange is one of the most important fruit produced in Syria, but the storability of the orange fruit is not well known. To determine the storability, and the effect of gamma irradiation on storability of orange fruits, Valencia orange fruit were subjected to gamma irradiation doses of 0.5, 1.0, and 1.5 kGy using gamma 60Co irradiator facility. Fruits were kept in a refrigerator (1-4 0C), and the humidity (80 – 90%). Weight losses, spoilage, total losses, and the skin deterioration were evaluated at 6, 12, and 18 weeks. The results indicated that the storability of orange fruits produced in Syria is not well according to the high weight loses and skin damages. There was a negative effect of gamma irradiation on storability of orange fruits. Therefore more studies are need to evaluate the effect of environment and production factors on storability of orange fruit, and to determine the best harvest time and storage conditions.